Gene expression in fungi - A. Kalkanci; A. Kadioglu; D. Wilson; M.D. Jacobsen (IMA Fungus)
This contribution is based on the four presentations made at the Special Interest Group (SIG) meeting titled Gene Expression in Fungi held during IMC9 in Edinburgh. This overview is independent from other articles published or that will be published by each speaker. In the SIG meeting, basic principles of in vivo animal models for virulence studies were discussed. Infection associated genes of Candida albicans and fungal adaptation to the host was summarized. Azole susceptibility was evaluated as a combined result of several changes in expression of pertinent genes. Gene transfer in fungi, resulting in fungal evolution and gene adaptation to environmental factors, was reported.